Comparative study of milk microbiota and metabolome in long-lived dairy cows with different persistent production capacities - Yang, Jianhao; Yuan, Naihan; Guo, Tengfei; Feng, Yanfei; Guo, Shanshan; Zhou, Dong; Lin, Pengfei; Wang, Aihua; Jin, Yaping (Frontiers in Microbiology, 2026)
Improving dairy cow lifespan is essential for sustainable livestock production. The milk microbiome and metabolome are closely associated with mammary gland health and influence the persistent productivity of dairy cows. However, the characteristics of the milk microbiome and metabolome underlying persistent productivity remain unknown. In this study, 16S rRNA sequencing and untargeted metabolomics were applied to evaluate the milk microbiome and milk metabolome composition of long-lived, high-yielding cows (LH) and long-lived, low-yielding cows (LL). The results showed that no significant differences were observed in the α- and β-diversity of milk microbiota between the two groups (p > 0.05). However, the community assembly processes differed significantly. The LH group exhibited significantly higher levels of homogeneous selection, drift (and others) (p < 0.05). In contrast, dispersal limitation, homogeneous dispersal, and heterogeneous selection were significantly lower (p < 0.05). In addition, in the milk of LH cows, UCG-005, Prevotellaceae UCG-003, Ruminococcus, unclassified f Oscillospiraceae, norank f Fodinicurvataceae, and unclassified f Ruminococcaceae were significantly enriched (LDA > 2, p < 0.05). The bacterial functions of protein digestion and absorption and N-glycan biosynthesis were significantly enriched in the LH group, while thyroid hormone synthesis and pathogenic Escherichia coli infection were significantly enriched in the LL group (LDA > 2, p < 0.05). Additionally, the milk of LH cows exhibited elevated levels of omega-3 polyunsaturated fatty acids (PUFAs), including PE (20:5/0:0), LPC (20:5 (5Z, 8Z, 11Z, 14Z, 17Z)/0:0), LPE (0:0/20:5 (5Z, 8Z, 11Z, 14Z, 17Z)), and PE (22:5/0:0) (LDA > 2, p < 0.05). Milk PE (18:3/0:0) showed a significant positive correlation with milk Prevotellaceae UCG-003 and UCG-005 (|r| > 0.50, p < 0.05). These bacterial genera were significantly negatively correlated with the predicted microbial function pathogenic E. coli infection (|r| > 0.50, p < 0.05). The accumulation of omega-3 PUFAs in milk may help maintain the homeostasis of mammary microbial environment and promote mammary health. These results provide novel insights into the microbial and metabolic signatures underlying persistent productivity, offering potential targets for nutritional and microbial interventions to enhance dairy cow longevity.